Guide to negotiating and formulating projects in networks - Project Management Unit (Inter-American Institute for Cooperation on Agriculture, 2022)
This document is intended to provide guidance to those seeking to formulate projects, by harnessing the tools established in the Business Model, based on lessons learned from formulation processes. It also speaks to the use of best practices for project management.